2016
DOI: 10.3856/vol44-issue1-fulltext-14
|View full text |Cite
|
Sign up to set email alerts
|

Produccion de compuestos fenolicos por cuatro especies de microalgas marinas sometidas a diferentes condiciones de iluminacion

Abstract: RESUMEN.Algas y microalgas son productoras de compuestos antioxidantes como respuesta protectora al daño producido por estrés (radiación UV, variación de temperatura, iluminación excesiva, entre otros). En el presente estudio, se evaluó en condiciones de laboratorio el contenido de fenoles totales en cuatro especies de microalgas marinas: Chaetoceros muelleri (Lemmermann, 1898), Thalassiosira weissflogii (Grunow, 1977), Dunaliella tertiolecta (Butcher, 1959) y Tetraselmis chuii (Butcher, 1959), sometidas a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…According to our results, DBP changes as a function of seasonal variations and it would be affected by CT and PAR, since there is a direct correlation with them. Authors such as Gomez et al (2016) mentioned that the relationship between light intensity and photosynthesis rate are independent of temperature at low intensities (< 100 µmol m − 2 s − 1 ). It depends on the dark reactions of photosynthesis and the level of nutrients.…”
Section: Biomass Productivitymentioning
confidence: 99%
“…According to our results, DBP changes as a function of seasonal variations and it would be affected by CT and PAR, since there is a direct correlation with them. Authors such as Gomez et al (2016) mentioned that the relationship between light intensity and photosynthesis rate are independent of temperature at low intensities (< 100 µmol m − 2 s − 1 ). It depends on the dark reactions of photosynthesis and the level of nutrients.…”
Section: Biomass Productivitymentioning
confidence: 99%
“…In some cases, these are not influencing factors. Gómez et al [ 52 ] observed that the accumulation of phenolic compounds in some microalgae was independent of the illumination condition. The production of flavonoids and polyphenols could be favored with the adequate control of selected variables of the culture process [ 12 ].…”
Section: Marine Phenolics: Sources and Phenolic Compositionmentioning
confidence: 99%